A COMPARATIVE STUDY ON SOME MAJOR CONSTITUENTS OF KARKADE (HIBISCUS SABDARIFFA L. – ROSELLE PLANT): Life Science-Biology - ABDALLAH MOHAMMED AHMED, FATIMA; MOHAMMED ELHASAN SATTI, NUHA; ELDIN HUSSAIN ELTAHIR, SHARAF (International Journal of Life Science and Pharma Research, 2019)
Hibiscus sabdariffaplant{Botanical name: Hibiscus sabdariffa Linne (Malvaceae)},commonly known as "rossell" in the English language, and "karkade" in Arabic. It is a plant widely cultivated in both tropical and subtropical regions including Sudan, (Kordofan and Darfur regions). Karkade calyces are used as a cold or hot drink when soaked in water, having refreshing, nutritional and medicinal characteristics. This study aimed at investigating the levels of some major constituents of the rossell calyces and compares their levels within the two varieties (Red and white calyces). The phytochemical, proximate and the specific analyses showed that the calcium levels in Sudanese karkade (25 mg/100g and 25.5 mg/100g in red calyces and white calyces, respectively) were lower than the levels reported by the previous studies, but the iron levels (55.5 mg/100g and 30.5 mg/100g ) were higher than levels reported by the previous studies. More investigations may be required to interpret this low level of calcium in some Sudanese karkade varieties. The anthocyanin levels (1.8% and 1.05% in red calyces and white calyces, respectively), and the vitamin C levels (16.5 mg/100g and 16.9 mg/100g) were approximately similar in both red and white karkade calyces, but the level of hibiscus acid of the red calyces was lower than its level in the white karkade calyces. The notable variations between results reported in literature about karkade (Hibiscus) constituents may be due to some factors include the variations of the genotypes, environmental and botanical nature of the tested samples, besides the use of different methodologies by researchers concerning laboratory techniques and the sampling collection methods